ANALISIS PRODUKSI, IMPOR DAN KONSUMSI KOMODITI BERAS DI INDONESIA - Rahma Yulnita; Yeniwati Yeniwati (Universitas Negeri Padang, 2019)
The research conducted aims to determine the effect of: (1) Rice Production Against Rice Imports in Indonesia; (2) Rice Production Against Rice Consumption in Indonesia; (3) Imports of Rice Against Rice Consumption in Indonesia. The type of this research is descriptive and associative research, and the data used is time series data with the research period 1985-2016. Data collection techniques used are documentation techniques, literature studies, publications from the Ministry of Agriculture in the form of Rice Outlook, and publications from Indonesian Central Bureau of Statistics. In this study the data analysis used is Descriptive Analysis and Inductive Analysis which consists of: Simple Linear Regression, Classical Assumption Test, and Determination Coefficient (R2). While the analysis in this study uses E-Views 8. The results of this study indicate that (1) Rice production has a significant and positive effect (prob = 0.0010 <α = 0.05) on rice imports in Indonesia with an influence level of 5.821536 (2) Rice production has a significant and negative effect (prob = 0.0063 <α = 0.05) on rice consumption in Indonesia with the level of influence of (-0.089005). (3) Rice imports have a significant and negative effect (prob = 0.0321 <α = 0.05) on rice consumption in Indonesia with an influence level of (-0.016228). Based on the results of the research that has been done, it is suggested to the government: (1) In the future the government is expected to be able to stabilize rice prices in Indonesia, perhaps by determining the price of rice circulating in the market and this will affect the welfare of the people in Indonesia must be done to help the consumption of the poor in Indonesia; (2) It is expected that the government does not import rice anymore because Indonesia is an agricultural country engaged in the agricultural sector; (3) It is expected to be able to adjust the availability of food, namely rice stocks in the country and not so much that the rice stock exceeds the amount of rice stock set by the government.